Analysis Study of Geriatric Syndrome and Frailty Prevalence in Older Adults: A Systematic Review and Meta-Analysis - Pretika Prameswari; Yudhi Hajianto Nugroho; Mutia Juliana (The International Journal of Medical Science and Health Research, 2025)
Background: Geriatric syndromes and frailty are major public health concerns associated with adverse health outcomes in aging populations worldwide. Frailty is a multifactorial condition characterized by increased vulnerability to stressors, leading to higher risks of morbidity, functional decline, hospitalization, and mortality. Objective: This meta-analysis aims to evaluate the prevalence, risk factors, and outcomes of frailty in older adults, as well as the effectiveness of various interventions in mitigating its impact. Methods: A systematic literature search was conducted across major databases to identify studies assessing frailty and geriatric syndromes. Studies were screened based on predefined eligibility criteria, and data were extracted for pooled analysis. Results: The findings indicate that frailty prevalence varies widely across different populations and is strongly associated with advanced age, comorbidities, malnutrition, and sedentary lifestyles. The pooled odds ratio for frailty versus robustness was 0.17 (95% CI: 0.16–0.18, p < 0.00001), indicating a strong negative association, with frail individuals being significantly more vulnerable to adverse health outcomes. However, substantial heterogeneity was observed across studies (I² = 100%), likely due to variations in frailty assessment tools, study populations, and geographic settings. Frailty prevalence ranged from 9.4% in rural Malaysia to 47.1% in Botswana, reflecting socioeconomic and healthcare disparities. Common risk factors included advanced age, female gender, chronic diseases, physical inactivity, and malnutrition. Conclusion: Addressing geriatric syndromes and frailty requires a holistic, multidisciplinary approach integrating early detection, prevention, and individualized interventions. Public health strategies and policy reforms should prioritize frailty screening, community-based support, and interdisciplinary care coordination to enhance the well-being of older adults and alleviate the burden on healthcare systems. Future research should focus on optimizing frailty management strategies and evaluating long-term outcomes in diverse populations.